Kejang Demam Sederhana pada Cerebral Palsy - Safiratul Izzati; Mardiati Mardiati (Natural: Jurnal Pelaksanaan Pengabdian Bergerak bersama Masyarakat., 2025)
Cerebral palsy (CP) is a permanent, non-progressive motor disorder that occurs due to brain damage experienced before, during, or after birth. This condition is generally characterized by activity limitations and can be accompanied by various other disorders, such as delayed cognitive development, visual impairment, speech disorders, and neuromuscular disorders. Management of cerebral palsy is usually multidisciplinary, including physiotherapy, behavioral therapy, speech therapy, nutritional management, pharmacotherapy, and surgical intervention, with the aim of improving the patient's quality of life. This case report discusses a male patient, An. AZ, aged 4 years and 6 months, who was brought by his parents to the Emergency Department of Cut Meutia General Hospital, North Aceh with the chief complaint of seizures that had occurred two days before admission and had worsened in the past day. The patient had been diagnosed with cerebral palsy since early childhood and regularly underwent physiotherapy. From the anamnesis, it was revealed that the patient experienced weakness on the left side of the body, which was more dominant than the right side. This condition is consistent with the manifestation of hemiplegia in cerebral palsy patients. Physical examination revealed delayed motor development, increased muscle tone on the left side, and enhanced pathological reflexes. Acute seizure management included administering anticonvulsant medication according to protocol, monitoring vital signs, and close observation in the inpatient ward. In addition to pharmacological therapy, the patient was advised to continue regular physiotherapy to maintain motor function, prevent contractures, and support the development of daily activities. This case emphasizes the importance of a comprehensive approach to the management of cerebral palsy, particularly when complicated by seizures. Integration of acute medical care, rehabilitative therapy, and family support plays a crucial role in improving the patient's quality of life.